Remote Eye Triage: Health Economic Perspectives on Resource Prioritization - Casper van der Zee; Robert P. L. Wisse; Saskia M. Imhof; Miriam P. van der Meulen (Health Services Insights)
Background: The TeleTriageTeam (TTT) is a novel system for remote eyecare delivery. Objectives: Explores the impact of TTT on costs by depicting program theory of care prioritization. Moreover, a quantification of longer-term effects of delay (and inversely earlier treatment) on costs is performed. Design: Mixed-methods health economic evaluation. Methods: First, we depicted the program theory of prioritization into a LOGIC-model using existing TTT-data and expert interviews outlining the causal pathways how and why a program is expected to work. Second, we identified the most relevant key diagnoses to be appraised based on incidence, severity, and presumed triage impact. Third, we estimated the impact of delay (or inversely earlier treatment) on societal costs and quality of life (QoL) based on literature searches. Cost data were updated to 2023. Results were reported per delayed patient per 6 months (the average TTT delay). Results: Five key diagnoses were selected: cataract, diabetic retinopathy (DRP), age-related macular disease (AMD), glaucoma, and dry-eye-syndrome (DES). The LOGIC-model showed how the TTT actions could influence costs and QoL. Semi-structured interviews revealed delay results in adverse events, at the expense of shorter waiting times in prioritized patients, and overall decreases personnel burden. Reduced waiting times were also believed to decrease burden and costs in prioritized patients. Literature showed that a delay in glaucoma treatment results in savings (−€409), while the other diagnoses suggested higher societal costs (cataract €3298, DES €2156, AMD €1455, DRP €117). QoL reduction and increased costs due to delay were more apparent when delay results in longer duration of curable symptoms compared to delay in stable disease (up to 0.09 vs 0.003 QALYs and €3298 vs €1455, respectively). Conclusions: Eye care delay results reduced QoL and increased societal costs, yet this is compounded by gains attributable to justified prioritization of more urgent and more severe patients.